2001
DOI: 10.1159/000047700
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Recurrent Strokes in Patients with Different Subtypes of Stroke: A Fourteen-Year Follow-Up Study

Abstract: In this study, 339 patients (154 men, 185 women) with a median age of 74 years (range 23–97) admitted to the Stroke Unit, Department of Neurology in 1986, have been followed up for 14 years. The diagnoses were intracerebral hemorrhage (ICH; 30, 8.8%), cardioembolic cerebral infarction (CE, 71, 20.9%), lacunar infarction (LI; 47, 13.9%) and atherosclerotic cerebral infarction (ACI; 191, 56.3%). The cumulative probabilities of recurrent stroke rates at 1-, 5- and 10-year follow-ups were 13.5% (95% confidence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
86
7
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 41 publications
10
86
7
3
Order By: Relevance
“…In addition, the 90-day survival rates of ischemic stroke patients noted in this study (92%) were slightly higher than those obtained from another medical center in Taiwan (Chang et al 2006). The one-year survival rates for cerebral hemorrhage (71%) and cerebral infarction (84%) in this study were higher than those of studies conducted in Perth, Australia (Anderson et al 1994) and in the Arcadia region of Greece (Vemmos et al 2000) but comparable to those conducted in Hong Kong (Wong and Li 2003), Canada (Saposnik et al 2008), and Sweden (Eriksson and Olsson, 2001). Age appears to be the most important predictor of the one-year mortality of stroke patients; however, a number of previous studies (Anderson et al 1994;Vemmos et al 2000;Eriksson and Olsson 2001;Wong and Li 2003) have not reported the exact risk estimates for various age levels.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In addition, the 90-day survival rates of ischemic stroke patients noted in this study (92%) were slightly higher than those obtained from another medical center in Taiwan (Chang et al 2006). The one-year survival rates for cerebral hemorrhage (71%) and cerebral infarction (84%) in this study were higher than those of studies conducted in Perth, Australia (Anderson et al 1994) and in the Arcadia region of Greece (Vemmos et al 2000) but comparable to those conducted in Hong Kong (Wong and Li 2003), Canada (Saposnik et al 2008), and Sweden (Eriksson and Olsson, 2001). Age appears to be the most important predictor of the one-year mortality of stroke patients; however, a number of previous studies (Anderson et al 1994;Vemmos et al 2000;Eriksson and Olsson 2001;Wong and Li 2003) have not reported the exact risk estimates for various age levels.…”
Section: Discussioncontrasting
confidence: 57%
“…Our study also showed that heart failure may also be a predictor of the one-year mortality of patients with cerebral infarction but not of those with cerebral hemorrhage. Previous studies (Eriksson and Olsson 2001;Koton et al 2010) similarly reported that congestive heart failure is a significant predictor of mortality in stroke patients. A small number of heart-failure patients with cerebral hemorrhage may have underpowered the statistical analysis in this study.…”
Section: Discussionmentioning
confidence: 85%
“…This finding is comparable to data from other Asian countries such as Japan and China [1,13]. Studies on stroke in European and North American countries show a higher non-LAC burden [1,14]. Small vessel disease appears to be commoner in the Asian region than in the West.…”
Section: Discussionsupporting
confidence: 78%
“…Most early case-fatality risk factors for hemorrhagic and ischemic stroke are well-described in the literature 6,12 . Overall, we found that advanced age, diabetes and previous heart disease were associated with a high case-fatality rate at 28 days for the ischemic subtype.…”
Section: Discussionmentioning
confidence: 99%